Synthesis, physical-chemical properties and further transformation of 5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R-2,4-dyhydro-3Н-1,2,4-triazole-3-thiones - T. M. Kaplaushenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of this work was the synthesis of new highly effective and low-toxic substances in a series of 5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R1-2,4-dyhydro-3Н-1,2,4-triazole-3-thiones and its derivatives, and also establishment of physical-chemical properties of all synthesized compounds, as well as computer predictions.